Resistance to disease and pests of bananas through genetic improvement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
An international symposium on this subject will be held at Montpellier, France, from 7-9 September, 1992. It will be organized by the Centre de cooperation internationale en recherche agronomique Dour le developpement (CIRAD), with the help of the...